Carbon-ceramic composite crucible as well as preparation method and application thereof

By using carbon fiber preform and liquid-phase siliconization process to prepare carbon-ceramic composite crucible during the single crystal silicon drawing process, the problem of easy crystallization and corrosion of quartz crucible is solved, and the density and uniformity of carbon-ceramic composite crucible are achieved. Extended service life and reduced production costs.

CN119350053APending Publication Date: 2025-01-24HUNAN SHIXIN NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411473536.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

During the existing single crystal silicon drawing process, the quartz crucible is prone to crystallization, corrosion and has a short service life, resulting in low production efficiency and high cost.

Method used

The carbon fiber prefabricated body sedimentary carbon to form carbon carbon composite cymbals, and purified through liquid -phase seepage silicon, thermal treatment, and the high temperature of Fluoline atmosphere to prepare carbon ceramic composites with good dense and uniformity.

Benefits of technology

The density and uniformity of the carbon-ceramic composite crucible are achieved, the service life is extended, the production cost is reduced, and the single crystal silicon pulling process operation is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005095353390000071
    Figure BDA0005095353390000071
Patent Text Reader

Abstract

The invention discloses a carbon-ceramic composite crucible as well as a preparation method and application thereof, and the method comprises the following steps: performing vapor deposition of carbon on a carbon fiber preform to obtain a carbon-carbon composite crucible; and sequentially carrying out liquid-phase siliconing, heat treatment and purification on the carbon-carbon composite crucible to obtain the carbon-carbon composite crucible. According to the method, the carbon-carbon crucible is soaked in the silicon liquid, technological parameters are controlled, so that silicon can fully permeate into the carbon-carbon crucible, pyrolytic carbon in the crucible can completely react with the silicon, and finally the compact and uniform carbon-ceramic composite material crucible is obtained, and the method has the advantages of being easy and convenient to operate, low in preparation cost, high in production efficiency and suitable for industrial production. The obtained carbon-ceramic composite material crucible is excellent in comprehensive mechanical property and long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbon-ceramic composite crucible and a preparation method and application thereof, belonging to the technical field of thermal field components for single crystal silicon pulling furnaces. Background Art

[0002] At present, the production of single crystal silicon basically adopts the form of carbon-carbon crucible + quartz crucible. The quartz crucible is used as a carrier for silicon materials. Polycrystalline silicon is melted in the quartz crucible, and the single crystal silicon is pulled in this quartz crucible; the carbon-carbon crucible is mainly used for bearing and heat transfer. The quartz crucible is placed in the carbon-carbon crucible. However, during the production process of single crystal silicon pulling, the molten silicon will react with the quartz crucible to form SiO gas. The generated SiO gas will corrode the carbon components in the furnace and reduce the service life of related accessories. The quartz crucible is prone to crystallization during use, which will cause the crucible to crack and fail after crystallization, and cannot meet the requirements of long-term continuous production and use.

[0003] Chinese patent CN114368975A discloses a process for preparing pyrolytic carbon and SiC composite matrix by CVI process and infiltrating into carbon-carbon crucible to achieve densification and form carbon / carbon / silicon carbide composite crucible; Chinese patent CN102731119A discloses a process for using hydrogen as carrier gas, hydrogen or argon as dilution gas, and introducing trichloromethylsilane into chemical vapor reactor by bubbling method to chemically infiltrate silicon carbide to obtain carbon-carbon / silicon carbide composite crucible blank. However, the production cycle of these two methods is too long, batch production is not used, and the uniformity of silicon carbide cannot be guaranteed by this method. Summary of the invention

[0004] In view of the defects existing in the prior art, the first object of the present invention is to provide a method for preparing a carbon-ceramic composite crucible. The method is easy to operate and does not require designing different tooling according to the carbon-carbon crucible embryo, which greatly reduces the tooling cost. At the same time, the high-temperature immersion furnace cavity space is guaranteed, and multiple carbon-carbon crucible embryos can be siliconized at the same time, thereby improving production efficiency.

[0005] The second object of the present invention is to provide a carbon-ceramic composite crucible with good and uniform density and excellent comprehensive performance.

[0006] The third object of the present invention is to provide an application of a carbon-ceramic composite crucible, which is used as a thermal field component in single crystal silicon pulling, thereby avoiding contamination of the charging silicon liquid and simplifying the single crystal silicon pulling process operation.

[0007] In order to achieve the above technical purpose, the present invention provides a method for preparing a carbon-ceramic composite crucible, comprising: vapor-depositing carbon on a carbon fiber preform to obtain a carbon-carbon composite crucible; then sequentially subjecting the carbon-carbon composite crucible to liquid-phase siliconization, heat treatment and purification to obtain the crucible; the conditions for the liquid-phase siliconization are: the immersion time of the silicon liquid is 1 to 4 hours, the temperature is 1500 to 1800°C; and the vacuum degree is 100 to 1000Pa.

[0008] The key to the technical solution of the present invention is to use liquid phase siliconization to replace the vapor deposition process in the prior art and to utilize the mutual cooperation between the various processes. The specific principle is: first, a carbon fiber preform is prepared by needle punching, and the density is reasonably controlled so that the subsequent processes can proceed normally. Then, the carbon source gas is pyrolyzed into carbon at high temperature through the vapor deposition carbon process, which is evenly deposited in the voids of the carbon fiber preform to densify the material. Subsequently, through the liquid phase siliconization process, silicon liquid is evenly attached to the surface and pores of the carbon-carbon composite crucible, and a carbon-silicon reaction is generated to form silicon carbide to further improve the mechanical properties of the composite crucible. Then, through heat treatment at high temperature, excess residual silicon in the product is removed and the carbon-silicon reaction is promoted to make the infiltration more complete. Finally, the material is purified by high temperature purification in a Freon atmosphere to remove metal impurities and metal-rich impurities such as nitrogen and oxygen.

[0009] The inventors have found that the liquid phase siliconization in the present invention is to load silicon powder into a high-temperature impregnation furnace, vacuumize and heat to fully melt the silicon material into silicon liquid, and then place the processed carbon-carbon crucible into a high-temperature impregnation furnace filled with silicon liquid for impregnation. The conditions of liquid phase siliconization have an important influence on the mechanical properties of the carbon ceramic crucible. For example, if the melting and infiltration temperature is too low and the melting and infiltration time is too short, silicon and pyrolytic carbon cannot be fully reacted to obtain silicon carbide to block the pores and too much residual silicon will result in poor density and low mechanical properties. If the melting and infiltration temperature is too high and the melting and infiltration time is too long, it is easy to corrode the carbon fiber and cause serious reduction in product performance. In addition, the melting and infiltration must be carried out under vacuum conditions to promote the penetration of silicon.

[0010] As a preferred solution, the density of the carbon fiber preform is 0.3-0.8 g / cm 3. The present invention firstly controls the density of the carbon fiber preform, so that the subsequent process can proceed normally and obtain a carbon-ceramic composite crucible with excellent comprehensive performance. The density of the preform has a great influence on the liquid silicon infiltration reaction, the particle size, distribution uniformity and residual silicon content of the silicon carbide matrix in the material. If the density of the preform is too high, the interior of the preform is relatively dense, and the surface layer is easily blocked during deposition and closed pores are very easy to form. When the material is subjected to the infiltration process, the porosity of the carbon-carbon material is small, the silicon infiltration channel is small, and the volume expansion of silicon and pyrolytic carbon reaction is easily blocked, which ultimately leads to poor material density, many internal closed pores, and poor mechanical properties; if the density of the preform is too low, the porosity is high, the carbon fiber content is low, and the product is easy to deform. During infiltration, the silicon carbide and silicon contents in the carbon-ceramic composite crucible are high, the silicon volume expands greatly, and there are many fine cracks, which makes the material easy to expand along the cracks when subjected to force. If the silicon residue is large, the risk of fiber being corroded by silicon will increase, and the comprehensive performance of the carbon-ceramic composite crucible will be reduced.

[0011] As a preferred solution, the carbon source gas for vapor deposition is at least one of natural gas, methane and propylene; the carrier gas for vapor deposition is at least one of argon, nitrogen and hydrogen. The present invention preliminarily densifies the carbon fiber preform by vapor deposition.

[0012] As a preferred solution, the volume ratio of the carbon source gas to the carrier gas is (1.5-2.5):1. By controlling the volume ratio of the carbon source gas to the carrier gas, the pyrolytic carbon during vapor deposition can be evenly deposited around the carbon fiber fabric and in the pores, so that the material can achieve uniform densification. If the carrier gas ratio is too high, the total mixed gas volume increases under the same pressure, resulting in low deposition efficiency and easy surface sealing. If the carrier gas ratio is low, the carbon source gas concentration at the bottom of the mixed gas is high, which affects gas diffusion and is prone to uneven density.

[0013] As a preferred solution, the conditions of the vapor deposition are: time of 1 to 100 hours and temperature of 1000 to 1100°C. If the vapor deposition time is too short, the pyrolysis gas cannot be effectively deposited around the carbon fiber preform or in the pores, and the densification effect cannot be guaranteed, thereby affecting the final performance; if the vapor deposition time is too long, the density of the carbon-carbon composite material after vapor deposition is too high, and the pores of the product are seriously blocked, which seriously affects the subsequent process, resulting in low product density and poor performance. At the same time, the long time affects the production cycle.

[0014] As a preferred solution, the density of the carbon-carbon composite crucible is 1.3-1.6 g / cm 3The density of carbon-carbon composite materials is too high, and the pores of the products are seriously blocked, which seriously affects the subsequent melt infiltration process, resulting in low product density, poor density and poor mechanical properties. The density of carbon-carbon composite materials is too low, and they are easy to deform after melt infiltration. At the same time, the silicon carbide and silicon content in the carbon-ceramic composite crucible is high, the density is not high, and it is easy to corrode the carbon fiber, which eventually causes the comprehensive performance of the carbon-ceramic composite crucible to decline.

[0015] As a preferred solution, the heat treatment conditions are: temperature of 2000-2300°C, time of 1-6 hours, and vacuum degree of less than 300 Pa. The purpose of the heat treatment in the present invention is mainly to remove excess residual silicon inside the product by high temperature, and further promote carbon-silicon reaction to make the infiltration more complete.

[0016] As a preferred solution, the purification conditions are: the treatment temperature is 2000-2800°C in a Freon atmosphere for 1-20 hours. Since the product purity requirements are very high in the crystal pulling environment, it is necessary to remove metal impurities and non-metallic impurities such as nitrogen and oxygen in the material under high temperature conditions.

[0017] The present invention also provides a carbon-ceramic composite crucible obtained by the above-mentioned preparation method. The material has the characteristics of good density, high uniformity, excellent comprehensive performance and the like.

[0018] The present invention also provides an application of a carbon-ceramic composite crucible, and the material is used as a thermal field component in single crystal silicon pulling, which can avoid the contamination of the charging silicon liquid and simplify the single crystal silicon pulling process operation.

[0019] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0020] 1) In the process of immersing the carbon-carbon crucible in silicon liquid, silicon can fully penetrate into the carbon-carbon crucible, and the pyrolytic carbon in the crucible can react completely with silicon, and finally a dense and uniform carbon-ceramic composite material crucible is obtained.

[0021] 2) The present invention is not limited to the carbon-carbon crucible blank. As long as the height of the silicon liquid is sufficient, any shape of carbon-carbon crucible can be siliconized using the method of the present invention, and the uniformity of siliconization of the product can be effectively ensured.

[0022] 3) The preparation method of the present invention is easy to operate and does not require different tooling to be designed according to the carbon-carbon crucible embryo, which greatly reduces the tooling cost. At the same time, the high-temperature immersion furnace cavity space is guaranteed, and multiple carbon-carbon crucible embryos can be siliconized simultaneously, thereby improving production efficiency.

[0023] 4) Compared with the mode of using a quartz crucible plus a carbon-carbon crucible for single crystal silicon pulling on the market, the carbon-ceramic composite crucible provided by the present invention does not use a quartz crucible in the whole process, and there is no separation difficulty problem, which greatly reduces the production cost, shortens the production process, and prolongs the service life of the crucible. DETAILED DESCRIPTION

[0024] The following examples are only specific descriptions of the preferred embodiments of the present invention, and are not intended to limit the scope of implementation of the present invention. For ordinary technicians in the technical field, any improvements made without departing from the present invention should be deemed to be within the scope of protection of the present invention.

[0025] Example 1

[0026] The present embodiment provides a method for preparing a carbon-ceramic composite crucible, which comprises the following steps:

[0027] S1. Preparation of carbon fiber preform: The carbon fiber fabric and mesh layer are alternately stacked, and the carbon fiber preform is prepared by needle punching process with a density of 0.55g / cm 3 ;

[0028] S2. Vapor deposition: The carbon fiber preform was placed in a chemical vapor deposition furnace, and propylene and hydrogen were introduced. The volume ratio of propylene and hydrogen was 1.5:1. The deposition time was 80 h, the deposition temperature was 1000 °C, and the deposition pressure was 0.5 kPa. The density was 1.35 g / cm 3 Carbon-carbon composite crucible;

[0029] S3, machining: machining the carbon-carbon composite crucible obtained in step S2 to a crucible of required shape and size, with a height of 600 mm and an outer diameter of 700 mm;

[0030] S4, liquid phase siliconization: put silicon powder with a particle size of 0.1mm into a high-temperature impregnation furnace, vacuum heat to fully melt the silicon material into silicon liquid, and then put the processed carbon-carbon crucible into a high-temperature impregnation furnace filled with silicon liquid. The impregnation temperature is 1800℃, the pressure is 1kpa, and the impregnation time is 3h;

[0031] S5, heat treatment: heat the crucible after siliconization in step S4 to 2200° C. for 3 h under vacuum conditions (vacuum degree less than 300 Pa);

[0032] S6. Purification: Finally, in a Freon atmosphere, the temperature is raised to 2300°C and kept at this temperature for 5 hours for high-temperature purification to finally obtain a carbon-ceramic composite crucible.

[0033] Example 2

[0034] The present embodiment provides a method for preparing a carbon-ceramic composite crucible, which comprises the following steps:

[0035] S1. Preparation of carbon fiber preform: The carbon fiber fabric and mesh layer are alternately stacked, and the carbon fiber preform is prepared by needle punching process with a density of 0.6g / cm 3 ;

[0036] S2. Vapor deposition: The carbon fiber preform was placed in a chemical vapor deposition furnace, and propylene and hydrogen were introduced. The volume ratio of propylene and hydrogen was 2:1. The deposition time was 100 h, the deposition temperature was 1100 °C, and the deposition pressure was 0.5 kPa. The density was 1.55 g / cm 3 Carbon-carbon composite crucible;

[0037] S3, machining: machining the carbon-carbon composite crucible obtained in step S2 to a crucible of required shape and size, with a height of 600 mm and an outer diameter of 700 mm;

[0038] S4, liquid phase siliconization: put silicon powder with a particle size of 0.1mm into a high-temperature impregnation furnace, vacuum heat to fully melt the silicon material into silicon liquid, and then put the processed carbon-carbon crucible into a high-temperature impregnation furnace filled with silicon liquid. The impregnation temperature is 1800℃, the pressure is 500pa, and the impregnation time is 4h;

[0039] S5, heat treatment: heat the crucible after siliconization in step S4 to 2200° C. for 3 h under vacuum conditions (vacuum degree less than 300 Pa);

[0040] S6. Purification: Finally, in a Freon atmosphere, the temperature is raised to 2400°C and kept at this temperature for 4 hours for high-temperature purification to finally obtain a carbon-ceramic composite crucible.

[0041] Example 3

[0042] The present embodiment provides a method for preparing a carbon-ceramic composite crucible, which comprises the following steps:

[0043] S1. Preparation of carbon fiber preform: The carbon fiber fabric and mesh layer are alternately stacked, and the carbon fiber preform is prepared by needle punching process with a density of 0.55g / cm 3 ;

[0044] S2. Vapor deposition: The carbon fiber preform was placed in a chemical vapor deposition furnace, and propylene and hydrogen were introduced. The volume ratio of propylene and hydrogen was 1.5:1. The deposition time was 80 h, the deposition temperature was 1000 °C, and the deposition pressure was 0.5 kPa. The density was 1.35 g / cm 3 Carbon-carbon composite crucible;

[0045] S3, machining: machining the carbon-carbon composite crucible obtained in step S2 to a crucible of required shape and size, with a height of 600 mm and an outer diameter of 700 mm;

[0046] S4, liquid phase siliconization: put silicon powder with a particle size of 0.1mm into a high-temperature impregnation furnace, vacuum heat to fully melt the silicon material into silicon liquid, and then put the processed carbon-carbon crucible into a high-temperature impregnation furnace filled with silicon liquid. The impregnation temperature is 1800℃, the pressure is 1kpa, and the impregnation time is 1.5h;

[0047] S5, heat treatment: heat the crucible after siliconization in step S4 to 2200° C. for 3 h under vacuum conditions (vacuum degree less than 300 Pa);

[0048] S6. Purification: Finally, in a Freon atmosphere, the temperature is raised to 2500°C and kept at this temperature for 3 hours for high-temperature purification to finally obtain a carbon-ceramic composite crucible.

[0049] Example 4

[0050] The present embodiment provides a method for preparing a carbon-ceramic composite crucible, which comprises the following steps:

[0051] S1. Preparation of carbon fiber preform: The carbon fiber fabric and mesh layer are alternately stacked, and the carbon fiber preform is prepared by needle punching process with a density of 0.55g / cm 3 ;

[0052] S2. Vapor deposition: The carbon fiber preform was placed in a chemical vapor deposition furnace, and propylene and hydrogen were introduced. The volume ratio of propylene and hydrogen was 1.5:1. The deposition time was 80 h, the deposition temperature was 1000 °C, and the deposition pressure was 0.5 kPa. The density was 1.35 g / cm 3 Carbon-carbon composite crucible;

[0053] S3, machining: machining the carbon-carbon composite crucible obtained in step S2 to a crucible of required shape and size, with a height of 600 mm and an outer diameter of 700 mm;

[0054] S4, liquid phase siliconization: put silicon powder with a particle size of 0.1mm into a high-temperature impregnation furnace, vacuum heat to fully melt the silicon material into silicon liquid, and then put the processed carbon-carbon crucible into a high-temperature impregnation furnace filled with silicon liquid. The impregnation temperature is 1600℃, the pressure is 1kpa, and the impregnation time is 3h;

[0055] S5, heat treatment: heat the crucible after siliconization in step S4 to 2200° C. for 3 h under vacuum conditions (vacuum degree less than 300 Pa);

[0056] S6. High-temperature purification: Finally, in a Freon atmosphere, the temperature is raised to 2500°C and kept at this temperature for 4 hours for high-temperature purification to finally obtain a carbon-ceramic composite crucible.

[0057] Comparative Example 1

[0058] In Comparative Example 1, the selection of the carbon fiber preform, the densification method, the machining, the high-temperature heat treatment and the purification are the same as those in Example 1, except for the siliconizing method.

[0059] Siliconization and densification: Silicon powder is laid on the bottom of the crucible in a vacuum high-temperature furnace. The amount of silicon added is based on the density of the carbon ceramic crucible of 2.4g / cm 3 According to the calculation, silicon powder with a particle size of 0.11 mm is filled in, the filling amount is 45 kg, the carbon-carbon crucible is placed on the crucible, the heating process is selected to be 1800℃, the insulation time is 3h, and the vacuum is required to be evacuated to the ultimate vacuum of the furnace chamber.

[0060] Comparative Example 2

[0061] S1. Preparation of carbon fiber preform: The carbon fiber fabric and mesh layer are alternately stacked, and the carbon fiber preform is prepared by needle punching process with a density of 0.9g / cm 3 ;

[0062] S2. Vapor deposition: The carbon fiber preform was placed in a chemical vapor deposition furnace, and propylene and hydrogen were introduced. The volume ratio of propylene and hydrogen was 1.5:1. The deposition time was 80 h, the deposition temperature was 1000 °C, and the deposition pressure was 0.5 kPa. The density was 1.35 g / cm 3 Carbon-carbon composite crucible;

[0063] S3, machining: machining the carbon-carbon composite crucible obtained in step S2 to a crucible of required shape and size, with a height of 600 mm and an outer diameter of 700 mm;

[0064] S4, liquid phase siliconization: put silicon powder with a particle size of 0.1mm into a high-temperature impregnation furnace, vacuum heat to fully melt the silicon material into silicon liquid, and then put the processed carbon-carbon crucible into a high-temperature impregnation furnace filled with silicon liquid. The impregnation temperature is 1800℃, the pressure is 1kpa, and the impregnation time is 3h;

[0065] S5, heat treatment: heat the crucible after siliconization in step S4 to 2200° C. for 3 h under vacuum conditions;

[0066] S6. Purification: Finally, in a Freon atmosphere, the temperature is raised to 2300°C and kept at this temperature for 5 hours for high-temperature purification to finally obtain a carbon-ceramic composite crucible.

[0067] Table 1: Performance test results of carbon-ceramic composite crucibles prepared in Examples 1 to 4 and Comparative Examples 1 to 2

[0068]

Claims

1. A method for preparing a carbon-ceramic composite crucible, characterized in that: The carbon fiber preform is subjected to vapor deposition of carbon to obtain a carbon-carbon composite crucible; Then the carbon-carbon composite crucible is sequentially subjected to liquid phase siliconization, heat treatment and purification to obtain; The conditions of the liquid phase siliconization are: the immersion time of silicon liquid is 1 to 4 hours, the temperature is 1500 to 1800° C., and the vacuum degree is 100 to 1000 Pa.

2. The method for preparing a carbon-ceramic composite crucible according to claim 1, characterized in that: The density of the carbon fiber preform is 0.3-0.8 g / cm 3 .

3. The method for preparing a carbon-ceramic composite crucible according to claim 2, characterized in that: The carbon source gas for vapor deposition is at least one of natural gas, methane and propylene; The carrier gas for the vapor deposition is at least one of argon, nitrogen and hydrogen; The volume ratio of the carbon source gas to the carrier gas is (1.5-2.5):

1.

4. The method for preparing a carbon-ceramic composite crucible according to claim 1 or 3, characterized in that: The conditions of the vapor deposition are: time of 1 to 100 hours and temperature of 1000 to 1100°C.

5. The method for preparing a carbon-ceramic composite crucible according to claim 1, characterized in that: The density of the carbon-carbon composite crucible is 1.3-1.6 g / cm 3 .

6. The method for preparing a carbon-ceramic composite crucible according to claim 5, characterized in that: The heat treatment conditions are: temperature of 2000-2300° C., time of 1-6 hours, and vacuum degree of less than 300 Pa.

7. The method for preparing a carbon-ceramic composite crucible according to claim 2, characterized in that: The purification conditions are: the treatment temperature is 2000-2800° C. and the treatment time is 1-20 hours in a Freon atmosphere.

8. A carbon-ceramic composite crucible, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

9. The use of a carbon-ceramic composite crucible according to claim 8, characterized in that: Used as a thermal field component in single crystal silicon pulling.

Citation Information

Patent Citations

  • Crucible using carbon / carbon / silicon carbide composite material and preparation method thereof

    CN102731119A

  • Low-density C / C-SiC composite material crucible containing alpha-Al2O3 coating

    CN114368975A

  • Carbon / silicon carbide composite material crucible preparation method

    CN103553692A

  • Method for preparing C / C-SiC composite part and product prepared through method

    CN106927846A

  • High-density high-purity carbon ceramic crucible and preparation method thereof

    CN117550909A